Political Party Funding Problems: Studies on PPP And PERINDO Parties in West Java - Arlan Siddha; Angga Nurdin Rachmat (Universitas Sultan Ageng Tirtayasa, 2023)
Political parties have a fundamental role in democracy. This fundamental role ultimately places political parties in a vulnerable and strategic situation. On the one hand, political parties must compete strictly with funding that is not small, and on the other hand, the presence of fund donors can erode the function of political parties as a liaison between society and the state. The theory used in this article is about political parties, especially funding for political parties. The method used is a qualitative research method with descriptive analysis. The data sources in this article are primary data through interviews with political party officials and secondary data through financial reports and literature studies from journals, news, and other articles. The results of this study indicate that parties that get small votes in political contestation in West Java experience problems in terms of carrying out political education and operational activities due to the lack of sources of funding for political parties. This situation causes political parties to only be able to organize political education internally due to the availability of existing funding. The impact of this situation is that the role of political parties does not work in providing political education to the community, which in turn has an impact on the political participation of the community, which is less effective.